Problem-Based Learning and Mind Mapping: Boosting Creativity in Architecture Education - Eko Nursanty; Rahmawaty Abu Hasan; Thazin Htet (Universitas 17 Agustus 1945, 2022)
This paper focuses on unlocking the creative potential of architecture students through an exploration of the Four C model of creativity. This model extends the traditional understanding of creativity and offers a comprehensive framework for fostering innovation in architecture. It introduces